2014
DOI: 10.1039/c3np70087a
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and site-selective derivatizations of natural products enabling biological studies

Abstract: Bioactive natural products and derivatives remain an enduring starting point for the discovery of new cellular targets for disease intervention and lead compounds for the development of new therapeutic agents. The former goal is accomplished through the synthesis of bioactive cellular probes from natural products enabling insights into the mechanism of action of these natural products by classical affinity chromatography or more recent proteome profiling methods. However, the direct and selective modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
111
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 80 publications
0
111
0
4
Order By: Relevance
“…Intermediate II′ differs from II in that its counterion is the non-coordinating B(C 6 F 5 ) 4 − instead of the reactive H−B(C 6 F 5 ) 3 − . 13 C{ 1 H} NMR spectroscopy revealed that the symmetric 3c converts to an asymmetric species with two methyl groups and four trisubstituted CH centres (Fig. 3a).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Intermediate II′ differs from II in that its counterion is the non-coordinating B(C 6 F 5 ) 4 − instead of the reactive H−B(C 6 F 5 ) 3 − . 13 C{ 1 H} NMR spectroscopy revealed that the symmetric 3c converts to an asymmetric species with two methyl groups and four trisubstituted CH centres (Fig. 3a).…”
Section: Resultsmentioning
confidence: 98%
“…The number of products that could be accessed from ring-opened or ring-closed sugars by controlling the positional selectivity of a deoxygenation process is significant, and such products would have the properties of a fine or specialty chemical. The possibility of synthesizing multiple high-value materials by controlling the deoxygenation of a small number of base carbohydrate feedstocks is appealing but poorly supported by the literature, although the chemoselective functionalization of complex polyols is an emerging field of considerable importance [13][14][15][16][17][18] .…”
mentioning
confidence: 99%
“…Even today, the importance of natural products as drug leads cannot be overstated. They continue to account for the majority of antimicrobial and anticancer agents approved by the FDA 2 while similarly serving as indispensable molecular probes in illuminating fundamental cellular processes 3 . Nevertheless, the pharmaceutical industry has severely pulled back its support for natural products research in recent decades in favor of synthetic approaches in building chemical libraries that are more suitable for modern biological screening campaigns.…”
mentioning
confidence: 99%
“…In recent years, catalyst dependent diversification of complex drug molecules has gained considerable interest. 8-11 Many important approaches, including biocatalysis, may be brought to bear on the problem. 12 …”
Section: Introductionmentioning
confidence: 99%